Ancient schwannoma mimicking a thyroid mass with retrosternal extension. (3rd September 2013) - Pillai, Suresh; Agarwal, Ashish Chandra; Mathew, Mary; Nayak, Dipak Ranjan
Abstract : We report the case of a middle-aged hypothyroid woman presenting with a neck swelling, voice change and breathing difficulty. On evaluation, she was diagnosed to have goitre with retrosternal extension. The mass was surgically excised and a histopathological report of ancient schwannoma was obtained. A review of literature on schwannomas of the head and neck was carried out. An ancient schwannoma should be considered as one of the differential diagnosis of a cervical mass, even though the clinical presentation point towards a thyroid swelling. At 6 months follow-up, the patient was found to be asymptomatic except for a hoarse voice.